The effect of colchicine on myocardial infarction: An updated systematic review and meta-analysis of randomized controlled trials - Ayesha Younas (7114868) (2025)
Introduction Myocardial infarction (MI) is associated with a significant post-event inflammatory response which further contributes to post-MI prognosis. Colchicine, an anti-inflammatory agent, exhibits potential benefits in various cardiovascular conditions such as coronary artery disease, pericarditis and atrial fibrillation. This meta-analysis predominantly aimed to provide an up-to-date evaluation of the efficacy and safety of colchicine in reducing adverse cardiovascular events in patients following acute MI. Methods A Comprehensive search was conducted on PubMed, Cochrane Library, Scopus, Google Scholar and clinicaltrials.gov for randomized controlled trials (RCTs) investigating the effect of colchicine on patients with MI from inception till May 2024. Our primary outcome was a composite of adverse cardiovascular events, while secondary outcomes included all-cause mortality, incidence of stroke, incidence of cardiac arrest, hospitalization urgency, incidence of recurrent MI, adverse gastrointestinal events and levels of high-sensitivity C - reactive protein (Hs-CRP). Risk ratios (RR) and mean differences (MD) were pooled under the random-effects model. Results Eleven trials with 7161 patients were included in our analysis out of which 3546 (49.51 %) were allocated to colchicine and 3591 (50.14 %) received placebo. Colchicine demonstrated statistically significant reduction in the composite of adverse cardiovascular events (RR = 0.75, 95 % CI: 0.60-0.94, P = 0.01, I2 = 47 %), and hospitalization urgency (RR = 0.46, 95 % CI: 0.31-0.68, P = 0.0001, I2 = 0 %) but statistically significant increment in adverse gastrointestinal events (RR = 1.86, 95 % CI: 1.14-3.02, P = 0.01, I2 = 79 %). However, all-cause mortality (RR = 1.00, 95 % CI: 0.72-1.39, P = 0.98, I2 = 0 %), incidence of cardiac arrest (RR = 0.81, 95 % CI: 0.33-1.95, P = 0.63, I2 = 0), incidence of stroke (RR = 0.45, 95 % CI: 0.17-1.19, P = 0.11, I2 = 36 %), incidence of recurrent MI (RR = 0.78, 95 % CI: 0.57-1.06, P = 0.11, I2 = 11 %) and the levels of hs-CRP (MD= -0.87, 95 %CI: -1.80-0.06, P=0.07, I2=67 % remained comparable across the two groups. Conclusion The use of colchicine post-MI reduces the composite of adverse cardiovascular events, and hospitalization urgency but increases adverse gastrointestinal events. However, colchicine does not impact all-cause mortality, cardiac arrest, stroke incidence, incidence of recurrent MI and the levels of hs-CRP. Large scale multicenter RCTs especially with longer follow-up duration are warranted to validate these findings. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102878